2014
DOI: 10.3390/f5092377
|View full text |Cite
|
Sign up to set email alerts
|

Local-Scale Mapping of Biomass in Tropical Lowland Pine Savannas Using ALOS PALSAR

Abstract: Fine-scale biomass maps offer forest managers the prospect of more detailed and locally accurate information for measuring, reporting and verification activities in contexts, such as sustainable forest management, carbon stock assessments and ecological studies of forest growth and change. In this study, we apply a locally validated method for estimating aboveground woody biomass (AGWB) from Advanced Land Observing Satellite (ALOS) Phased Array-type L-band Synthetic Aperture Radar (PALSAR) data to produce an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The larger overall overestimation found in Tahoe compared to Asiago is possibly due to the sparser tree cover characterizing this site, in which the SAR backscattering is therefore more influenced by the ground signal component. Viergever [59] also reported overestimation modeling biomass with SAR data in sparse savanna woodlands, while [60] suggested that pantropical carbon maps may overestimate AGB in savanna areas. However, underestimation of tree heights has also been reported for lidar-derived tree height models, and attributed to the laser beams missing the tree tops, especially at low laser point densities [61][62][63], even if there are several examples of AGB models developed with low point density lidar [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The larger overall overestimation found in Tahoe compared to Asiago is possibly due to the sparser tree cover characterizing this site, in which the SAR backscattering is therefore more influenced by the ground signal component. Viergever [59] also reported overestimation modeling biomass with SAR data in sparse savanna woodlands, while [60] suggested that pantropical carbon maps may overestimate AGB in savanna areas. However, underestimation of tree heights has also been reported for lidar-derived tree height models, and attributed to the laser beams missing the tree tops, especially at low laser point densities [61][62][63], even if there are several examples of AGB models developed with low point density lidar [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…There are vast areas covered by grassland and rangeland ecosystems in the tropics and subtropics, including savannas, and a large body of RS research has been conducted within these systems (Michelakis, Stuart, Lopez, Linares, & Woodhouse, 2014;Mutanga & Rugege, 2006;Paruelo et al, 2000;Sarrazin et al, 2011). Although this work has resulted in important methodological progress, many of the findings apply solely to the specific conditions of these ecosystems, and in most cases, they cannot be transferred to the grassland systems of moderate climates, which are typically managed more intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Several modeling approaches can be used to retrieve forest GSV (or AGB) from radar backscatter coefficients, including parametric and nonparametric models [3,[8][9][10]13,16,24,[37][38][39][40][41]. Within a previous study, some of these models were evaluated using the Romanian NFI and ALOS PALSAR-2 datasets [42].…”
Section: Growing Stock Volume Retrievalmentioning
confidence: 99%
“…Such limitations translate into discrepancies between in situ and mapped biomass stocks. Indeed, many studies have shown differences between the global products specified accuracy and in situ samples over national to regional scales [14,18,[21][22][23][24] with locally calibrated products providing significant improvements for the estimated forest parameters [14,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%